Plasma homocysteine levels in Indian patients with acute ischemic stroke - Alloli, Deepa; Mahishale, G. S.; Hanjagi, Siddaraya; Hussaini, Sayed Mohammed Meraj; Patil, Ganga (International Journal of Research in Medical Sciences, 2018)
Background: Homocysteine has primary atherogenic and prothrombotic properties. The present study aimed to assess serum homocysteine levels in patients with ischemic stroke and to find association of serum homocysteine levels with various patient related variables. Methods: This observational study included patients who were admitted with the diagnosis of stroke in Sri Ventateswara Ramnarain Ruia Government General Hospital. Patients were evaluated for risk factors like hypertension, diabetes mellitus and hyperlipidemia. Total homocysteine estimation was done and survival of the patients was assessed at the time of discharge from the hospital. Results: Most common risk factor for stroke in our study population was dyslipidemia (40%), followed by hypertension (36%). Total homocysteine levels were raised in 92% of the patients. Patients with homocysteine levels less than 15mM/L had lacunar infarcts. Homocysteine levels higher than 100mM/L were found in 18% of the patients and they all had large sized lesions. Significantly higher mean homocysteine levels were found among patients with large lesions (70.15±2.65 vs 21.68±8.02, p value <0.05). Among various risk factors, higher mean homocysteine levels were found to be associated with dyslipidemia (p value <0.05). No association between hypertension, diabetes mellitus or smoking history was found with higher homocysteine levels. Patients who survived had significantly lower homocysteine levels as compared to non survivors (39.3±19.84 vs 100±18.82, p value<0.001). Conclusions: Further studies are needed on homocysteine and stroke fur using homocysteine as screening test and for initiation of preventive therapy of stroke based on homocysteine levels.